Hunger free and healthy world by 2030 practice nutritionally smart and sustainable agriculture - Ali, Nawab (Indian Farming, 2018)
It may be summarized by saying that every human being born and living on the beautiful and dynamic planet earth, has full right to have the basic necessities of life such as food, clothes, shelter, education and medical aids and at the same time he or she has moral duty and responsibility to work as per his/her physical and intellectual ability/capacity in any one or more of livelihood sources e.g. agriculture, industry, trade or services. The respective national governments and international agencies have to work together and cooperate each other as per national and international rules and regulation and see that no citizen of the world go hungry or malnourished. As of now, the world is producing enough food for everyone but on account of postharvest losses and food wastages at various levels such as home, hostels, hotels, restaurants and so on, a sizeable proportion of world population suffer from hunger and malnutrition, especially those who do not have reasonable physical and financial access to food and other necessities of life. As of now, such people are 10 to 15% of the total global population. The need is to produce enough quality foods of plant and livestock origin using nutritionally smart, integrated and sustainable farming systems for which tools technology and resources are available, worldwide and make the world a healthy and happy place to live in and enjoy life and living by every citizen of the globe and leave enough quality natural resources for the coming generations.